2015
DOI: 10.1111/ijd.12888
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of tinea capitis in northeast Iran: a retrospective analysis from 1998 to 2012

Abstract: The present study showed that tinea capitis is mainly due to the anthropophilic species, and the most common species were T. tonsurans and T. violaceum. Owing to the high frequency of anthropophilic species, future studies may be useful in the development of preventive and educational strategies to reduce healthcare expenditure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 27 publications
1
12
0
Order By: Relevance
“…In the current study, the results of direct examination revealed that endothrix (69.6%) was more common than ectothrix (30.4%). While some studies [15, 18] have reported endothrix to be more common than ectothrix, others have demonstrated the higher prevalence of ectothrix [11, 19] based on KOH examination. This discrepancy could be related to the difference in the dominant dermatophyte species in various geographic areas.…”
Section: Discussionmentioning
confidence: 99%
“…In the current study, the results of direct examination revealed that endothrix (69.6%) was more common than ectothrix (30.4%). While some studies [15, 18] have reported endothrix to be more common than ectothrix, others have demonstrated the higher prevalence of ectothrix [11, 19] based on KOH examination. This discrepancy could be related to the difference in the dominant dermatophyte species in various geographic areas.…”
Section: Discussionmentioning
confidence: 99%
“…A completed detailed summary of all included of TC reported in the Asian continent 139–149 is shown in Table 3.…”
Section: Methodsmentioning
confidence: 99%
“…Although most dermatologists are familiar with TC in children, adults with TC are often neglected despite the increasing number of cases 2,3 . Adult TC only contributed 1.7% to 15.2% of cases in previous studies 4,5 . Why is adult TC uncommon?…”
Section: Introductionmentioning
confidence: 99%